الوصية الواجبة بين الشريعة الإسلامية وقانون ولاية سلانجور: دراسة تحليلية: The Obligatory Will between Shariah and Law of Selangor: An Analytical Study - Fatimah Karim (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2023)
ملخص البحث يهدف هذا البحث إلى دراسة موضوع "الوصية الواجبة بين الشريعة الإسلامية وقانون ولاية سلانجور: دراسة تحليلية". قد تناول البحث بيان تعريف الوصية ومشروعيتها في الإسلام. وتطرق البحث في توضيح حقيقة الوصية الواجبة وآراء الفقهاء في مشروعيتها، وإبراز تحليلات المواد القانونية المتعلقة بالوصية الواجبة تحت البند السابع والعشرين (27) قانون الوصايا للمسلمين بولاية سلانجور 1999م من منظور الفقه الإسلامي. تكمن أهمية البحث من أجل وصول إلى الحكم الشرعي الصحيح القائم على الدليل في الوصية الواجبة، وبيان أحكام الوصية الواجبة في بحث متكامل يسهل تناوله وتعم به الفائدة. تعتمد الباحثة على المنهج الاستقرائي، والمنهج الوصفي، والمنهج التحليلي؛ من أجل تتبع أقوال العلماء المعاصرين عن الوصية الواجبة، وتوضيح حقيقة الموضوع، وتحليلها من كافة جوانبها الشرعية. ومن النتائج المهمة من البحث أن الوصية الواجبة اجتهادًا من واضعي القانون مبنيًا على رعاية أولاد الأبناء والبنات الذين يموت آباءهم أو أمهاتهم في حياة أجدادهم، فيبتلون باليتم والحرمان من الميراث، مع غلبة الشح والأنانية في هذا العصر، فجبروا هذا بقانون الوصية الواجبة من أجل تحقيق العدالة بين أفراد الأسرة. ABSTRACT This research aims to study the topic of "The Obligatory Will between Shariah and Law of Selangor: An Analytical Study". The research deals with the definition of a will or testament and its legitimacy in Islam. The research explains the reality of obligatory will and evaluate the opinions of scholars on its legality and analyses the enactment of obligatory bequest under section 27 Muslim Wills (Selangor) Enactment 1999 from Islamic jurisprudence perspectives. The importance of the research is to arrive at the correct legal ruling of obligatory will based on evidence and clarify the provisions of the obligatory will in integrated research that is easy to deal with and beneficial. The researcher relies on the inductive method, descriptive method, and analytical method to examine the justification of jurists on obligatory will, to describe the obligatory will details and analyze it from Shariah perspectives. One of the important findings of the research is that the obligatory will is a will that implemented legally based on independent reasoning by expert in Islamic law, to take care of the children of sons and daughters whose fathers or mothers die during the life of their grandparents, that afflicted with orphanhood and deprivation of inheritance, with the predominance of greed and selfishness in this era, thus obligatory will is legally commanded to achieve justice among family members.